Anatomy for plastic surgery of the face, head, and neck - Watanabe, Kōichi, 1968- (Thieme, 2016)
The illustrations are in superb quality colour (as expected from this publisher), whether as diagrams, clinical photographs or cadaver dissection images. This is a very good basic science reference book for any surgeon in the field of head and neck -- The Journal of Laryngology & Otology Although the writing is both meticulous and comprehensive, the true strength of the book is the illustrations and dissections, which aid in giving the reader a great background into the realm of anatomy of the head and neck. -- Plastic and Reconstructive Surgery Anatomy for Plastic Surgery of the Face, Head, and Neck details the complex regional anatomy of the face, head and neck, providing plastic surgery and otolaryngology residents with a solid anatomical knowledge base. There are many danger zones involved in operating on the head and neck, and the detailed knowledge of anatomy that readers gain from this reference will help them avoid the surgical mishaps that often result in patient disfigurement.